Real-World Effectiveness of Vedolizumab vs Anti-TNF in Biologic-naïve Crohn's Disease Patients: A 2-year Propensity-score-adjusted Analysis from the VEDOIBD-Study. - Bokemeyer, Bernd; Plachta-Danielzik, Sandra; Di Giuseppe, Romina; Efken, Philipp; Mohl, Wolfgang; Hoffstadt, Martin; Krause, Thomas; Schweitzer, Axel; Schnoy, Elisabeth; Atreya, Raja; Teich, Niels; Trentmann, Leo; et al. (Inflammatory Bowel Diseases, 2024)
BACKGROUND: The aim of this observational, real-world evidence, modified intention-to-treat (mITT) study based on prospectively collected data from the VEDOIBD registry was to compare the effectiveness of vedolizumab (VEDO) vs antitumor necrosis factor (anti-TNF) in biologic-naïve Crohn's disease (CD) patients. METHODS: Between 2017 and 2020, 557 CD patients starting therapy with VEDO or anti-TNF were consecutively enrolled in 45 IBD centers across Germany. Per study protocol, the analysis excluded biologic-experienced patients and those with a missing Harvey-Bradshaw Index score, resulting in a final sample of 327 biologic-naïve CD patients. Clinical remission was measured using the Harvey-Bradshaw Index at the end of induction therapy and after 1 and 2 years. Switching to a different therapy was considered an outcome failure. Propensity score adjustment with inverse probability of treatment weighting was used to correct for confounding. RESULTS: The effectiveness of both VEDO (n = 86) and anti-TNF (n = 241) was remarkably high for induction treatment, but VEDO performed significantly less well than anti-TNF (clinical remission: 56.3% vs 73.9%, P < .05). In contrast, clinical remission after 2 years was significantly better for VEDO compared with anti-TNF (74.2% vs 44.7%; P < .05; odds ratio, 0.45; 95% CI, 0.22-0.94). Remarkably, only 17% of patients switched from VEDO to another biologic vs 44% who received anti-TNF. CONCLUSIONS: The results of this prospective, 2-year, real-world evidence study suggest that the choice of VEDO led to higher remission rates after 2 years compared with anti-TNF. This could support the role of VEDO as a first-line biologic therapy in CD.
EVALuna2:550726